Unmanned Aerial Vehicle (UAV)-Based for Slope Mapping and the Determination of Potential Slope Hazard - M. F., Zolkepli; M. F., Ishak; Z., Abu Talib (Penerbit UTHM, 2022)
This paper discusses the applications of unmanned aerial vehicle (UAV) for slope mapping and the determination of potential slope hazard of three selected areas. With the development of modern technology, the utilization of UAV to gather data for slope mapping can be considered as finest method as it is quick, reliable, precise, cost-effective and also easily to operate. High imagery quality is essential for the effectiveness and nature of normal mapping output such as Digital Surface Model (DSM) and also Ortho Images. The utilization of UAV to capture aerial photo helps to gather information from a normal area to an area which almost impossible to reach. With the data obtained by the UAV, it will later process in established software and the analysis of slope profile of certain selected study areas will be done. Mapping using UAV was within the area of Pahang Matriculation College. Three slope area namely as Area 1, Area 2 and Area 3 are marked. Further analyses are conducted in these three areas to obtain the information of potential slope hazard based on slope angles. For Area 1, the slope is marked at the coordinate of (286136.265, 412066.821) to (286265.423, 411783.038). The slope angle between the two vertexes was 46.18° and considered as very steep slope. For Area 2, the slope is marked at the coordinate of (286054.203, 412021.343) to (285963.651, 411913.543). The slope angle between the two vertexes was 77.66° and considered as very steep slope. The slope at Area 3 is marked at the coordinate of (285847.833, 411775.762) to (285887.450, 411251.046). The slope angle between the two vertexes was 47.43° and considered as very steep slope. In conclusion, the use of UAV in geotechnical engineering proven to be very useful for slope mapping and determination of slope hazard based on slope angle.